Famililism and welfare regimes: Poverty, employment, and family policies - Joya Misra; Stephanie Moller (Luxembourg Income Study (LIS), 2005)
While many nations lay a claim to supporting 'family values', these values may be interpreted in a variety of ways. How do nations support families, particularly families with children? What strategies do different nations take, and how do these strategies lead to different outcomes? In this paper, we show how different combinations of policies that support family caregiving and those that de-familialize caregiving lead to significantly different outcomes. We show that nations with stronger levels of both kinds of policies have lower poverty levels than those with weaker levels of these policies, but that strong levels of policies that support family caregiving and weak levels of de-familializing policies have more varied results, with higher levels of poverty, particularly for families headed by single mothers. In addition, this research illustrates significant variation among 'continental Conservative' countries, and suggests the importance of a less static approach to welfare state regimes, which also fully recognizes the centrality of gender relations to labor market and welfare state policies.
Keywords: 330; Familienpolitik; Einkommensverteilung; Öffentliche Sozialleistungen; Steuerbelastung; Gini-Koeffizient; Europa; Australien; Nordamerika